Play therapy : the art of the relationship - Landreth, Garry L. (New York, NY : Routledge, 2012)
'Play Therapy: The Art of the Relationship is a text for graduate-level counseling students in play therapy courses. It provides comprehensive and detailed information for creating therapeutic relationships with children and facilitating the play therapy process. Landreth stresses the importance of understanding the child's world and perspective, allowing play therapists to fully connect with them. Although there is this emphasis on the experiential aspect, the relevant research and theory are still considered. The author presents descriptions of play and the history of play therapy, child and therapist characteristics, play room set-up and materials, working with parents. Guidelines, transcripts, and case examples are provided for governing sensitive issues at every stage of the therapeutic process, from the first meeting to the end of the relationship. This new edition will incorporate the relevant research that has taken place since the publication of the previous, and includes new sections on supervision of play therapists, legal and ethical issues, and multicultural considerations in play therapy'--
'This is a text for graduate-level counseling students in play therapy courses. It provides comprehensive and detailed information for creating therapeutic relationships with children and facilitating the play therapy process. Landreth stresses the importance of understanding the child's world and perspective, allowing play therapists to fully connect with them'--
Includes index.
Keywords: Play Therapy; Play therapy